Assessment of Radioactivity in Building Materials: Implications for Health in Kurdistan Region of Iraq - Jafir, Adeeb O.; Hussein, Mohammed I.; Nadir, Idrees A.; Sabr, Barzan N.; Ahmed, Ali H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
This research investigates the radioactivity levels of various rock types used in construction within the Kurdistan region and assesses their potential impact on human health, the measurements were performed using an HPGe gamma-ray spectrometer. The measured activity concentrations of 226Ra, 232Th, and 40K radionuclides varied from ND (Chromitite) to 78.68 ± 4.54 Bq/kg (Marly Limestone), ND (Chromitite) to 109.52 ± 10.23 Bq/kg (Mudstone), and ND (Chromitite) to 2973.6 ± 152.1 Bq/kg (Claystone), respectively. The obtained Raeq values for all rock samples are well below the UNSCEAR, 2008 recommended value of 370 Bq/kg. 71.43% of DR, 66.66% of Eout, 71.43% of Ein, 100% of Hinand Hout, 71.43% of ELCRout, 71.43% of ELCRin, and 100% of activity utilization index of the rock samples are well below the recommended values declared by UNSCEAR, 2008. The radioactivity level of rock types that are prepared as building materials should be assessed by the producers and considered by the users to reduce the overall cancer risk. The outcomes of the RESRAD-BUILD computer code indicate that the maximum external and inhalation doses were calculated to be 19.7 and 0.105 μSv for R7 and R1 samples, respectively, over a period of 70 years.